9.7k views
4 votes
Exponents math help!

Exponents math help!-example-1

2 Answers

5 votes
ANSWER


\frac{ {m}^(2) {n}^( - 5) }{ {m}^( 7) {n}^( - 17) } = \frac{ {n}^(12) }{ {m}^(5) }



EXPLANATION


The given expression is


\frac{ {m}^(2) {n}^( - 5) }{ {m}^( 7) {n}^( - 17) }


Recall the following law of exponents,


\frac{ {a}^(m) }{ {a}^(n) } = {a}^(m - n)


We apply this law to obtain:




\frac{ {m}^(2) {n}^( - 5) }{ {m}^( 7) {n}^( - 17) } = {m}^(2 - 7) {n}^( - 5 - - 17)


This simplifies to,


\frac{ {m}^(2) {n}^( - 5) }{ {m}^( 7) {n}^( - 17) } = {m}^( 2- 7) {n}^( - 5 + 17)


\frac{ {m}^(2) {n}^( - 5) }{ {m}^( 7) {n}^( - 17) } = {m}^( - 5) {n}^( 12)

Recall again that,



{a}^( - m) = \frac{1}{ {a}^(m) }

This implies that,



\frac{ {m}^(2) {n}^( - 5) }{ {m}^( 7) {n}^( - 17) } = \frac{ {n}^(12) }{ {m}^(5) }

The correct answer is D.
User Kushal Paudyal
by
5.1k points
4 votes

Answer:

n¹²/m⁵

Explanation:

In indices; 1/a = a⁻¹

1/a⁻² = a²

So, with this information we can simplify the expression as shown bellow;

(m²n⁻⁵)/(m⁷n⁻¹⁷) = m²n⁻⁵m⁻⁷n¹⁷

= m²⁻⁷n⁻⁵⁺¹⁷

= m⁻⁵n¹²

= (n¹²)/(m⁵)

= n¹²/m⁵

The answer is D.

User Ian Dunn
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.